2021
DOI: 10.1177/03635465211016840
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of Δ9-Tetrahydrocannabinol (THC) and Cannabidiol (CBD), the Major Constituents of Cannabis, in a Sprague Dawley Rat Achilles Tendon Surgical Repair Model: A Pilot Study

Abstract: Background: The use of cannabis is common among athletes and the US population at large. Cannabinoids are currently being evaluated as alternatives to opioid medications for chronic pain management. However, the effects of recreational and/or medical use of delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) on musculoskeletal injury and healing remain largely unknown. Hypothesis/Purpose: The purpose of this study was to evaluate the biomechanical effects of CBD and THC on tendon-to-tendon healing in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“… 24 The mode of administration is an important consideration regarding cannabinoids, as previous studies have found that smoking increases the risk of failure after ARCR, 11 , 29 findings that could be relevant to inhaled forms of cannabis or CBD. In a recent animal model study investigating Achilles tendon-to-tendon repair, Stauch et al 36 compared biomechanical characteristics between a CBD group and control group and found no statistically significant differences in tendon strength, stiffness, or load to failure. While additional basic science research is necessary to elucidate the effect of CBD on soft tissue healing, the results of the current study provide additional evidence that CBD does not detrimentally effect recovery after soft tissue procedures.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The mode of administration is an important consideration regarding cannabinoids, as previous studies have found that smoking increases the risk of failure after ARCR, 11 , 29 findings that could be relevant to inhaled forms of cannabis or CBD. In a recent animal model study investigating Achilles tendon-to-tendon repair, Stauch et al 36 compared biomechanical characteristics between a CBD group and control group and found no statistically significant differences in tendon strength, stiffness, or load to failure. While additional basic science research is necessary to elucidate the effect of CBD on soft tissue healing, the results of the current study provide additional evidence that CBD does not detrimentally effect recovery after soft tissue procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Phytocannabinoids such as THC, CBD, and CBG have been found to demonstrate antinociceptive effects in animal models (Ward et al, 2011;Ward et al, 2014;;Henderson-Redmond et al, 2021;Stauch et al, 2021;Sepulveda et al, 2022a;Sepulveda et al, 2022b;Nachnani et al, 2023). Additionally, pain is a major issue for which patients report using medical cannabis and cannabis extracts (Alexander, 2016;Aviram and Samuelly-Leichtag, 2017;Legare et al, 2022).…”
Section: Antinociceptive Propertiesmentioning
confidence: 99%